Minimally Invasive Fixation with Dorsal Suspension Button and Volar Plate in Distal Radius Fractures with Dorsal Die Punch Fragments: A Preliminary Study - Miró, José Ignacio; Bensi, Alejo García; Rodríguez, Gustavo Luis Gómez; Clembosky, Gabriel (Journal of Wrist Surgery, 2022)
Objective The objective of the study is to analyze the clinical and radiological results obtained using a minimally invasive fixation technique with a volar locking plate and a suspension system with a dorsal button in distal articular radius fractures with dorsal comminution.Materials and Methods Six patients with distal radius fractures, between 19 and 68 years of age, were included in the study. Mean follow-up was of 15 weeks. Range of motion (ROM) in flexion, extension, radial deviation, ulnar deviation, pronation, supination, the strength in kilograms, and values on the Visual Analog Scale (VAS), Disabilities of Arm, Shoulder and Hand (DASH), and Mayo Wrist Score (MWS) scales were evaluated at 4, 8, and 12 weeks postoperative. Correction of anteroposterior diameter of the radius and concordance between postoperative anteroposterior diameter and the contralateral wrist diameter were evaluated radiologically.Results The following mean values were obtained at 12 weeks postoperative: ROM in flexion: 40.5°, ROM in extension: 49.5°, ROM in radial deviation: 24.5°, ROM in ulnar deviation: 15°, ROM in pronation: 87°, ROM in supination: 89°, strength: 37.5 kg, pain in VAS scale: 2 points, DASH: 54.5 points, and MWS: 67.5 points. At 12 weeks postoperative, the mean correction of anteroposterior diameter was 0.49 mm. The anteroposterior diameter and that of the contralateral wrist were strongly correlated.Conclusion Fixation with the volar locking plate and dorsal suspension button could be considered an alternative to dorsal plate fixation for treatment of distal radius fractures with comminution or associated dorsal die punch fragments.
Keywords: distal radius fractures; dorsal approach; specific fixation; volar plate